The Examination of Conscience: A Preliminary Study on the Effects on Metamemory After a 2-Week Practice - De Pisapia, Nicola; Dall’Avanzi, Martina (Frontiers in Psychology, 2022)
Examination of conscience is a contemplative practice that consists in examining daily the actions performed during the day (evening examination, immediately before going to bed) and the actions to be performed on the coming day (morning examination, immediately after sleep). While research on contemplative practices such as mindfulness has seen a large increase of studies in recent years, research into the psychological effects related to the practice of the examination of conscience has been largely ignored in the scientific literature. On the other hand, on a careful historical and philosophical analysis, it appears evident that references to it abound in many cultural contexts and in different eras. Here, we examined the effects of a two-week program of this practice that participants performed using a digital application developed ad hoc for this experiment. A control group performed an activity of the same duration, also with the support of a digital application, but which consisted of listening to audio excerpts of an Italian literary novel. Measurements taken from both groups before and after the two-week period consisted of self-assessments of metamemory capacity, that is, awareness and knowledge of their own memory processes. Results showed that participants reported a significant decrease in two properties of their metamemory after training, specifically vividness and coherence. No other significant changes were found between the two groups. Specifically, we found no differences in other metamemory characteristics, no differences in prospective or retrospective memory, and no differences in changes in stress levels.